Evidence-based clinical decision making for the management of patients with periodontal osseous defect after impacted third molar extraction: A systematic review and meta-analysis - Soo-Hoong Low; Sao-Lun Lu; Hsein-Kun Lu (Elsevier, 2021)
Background/purpose: Extraction of impacted mandibular third molar (MTM) is one of the most common procedures in clinical dental treatment; building a decision tree to perform MTM extraction can be prudent in alleviating periodontal diseases. This study is to review the latest research on the management of periodontal osseous defect (POD) after MTM extraction and rebuild a new clinical decision tree. Materials and methods: Current study was conducted according to PRISMA statement. Medline, Embase, Scopus, and Google Scholar were searched concerning treatment of MTM extraction up to Oct.2019. Three focused questions revolving around asymptomatic versus disease site, age, and necessity of ridge preservation after >6 months follow up will be answered. Results: A total of 7 studies were included for meta-analysis. Evidences were inadequate in regards to asymptomatic vs disease site of MTM extraction in the long-term follow-up. For patients with age <25 years, postoperative probing depth (PD) always remained at < 4 mm. However, for patients with age >25 years with initial PD > 7 mm, residual pockets still remained at 5 mm. For ridge preservation, significant positive effect in reduction of second molar distal site PD was observed, regardless of different biomaterials being placed (z = 4.69, p < 0.00001). Conclusion: Age is of utmost importance in preoperative evaluation during impacted MTM extraction. The timing for ridge preservation is essential determinant for achieving optimal treatment outcome. The clinical decision tree as proposed could serve as guidance when dealing with POD after impacted MTM extraction.